Peran Kerjasama Kepala Sekolah dengan Guru dalam Meningkatkan Kinerja Guru di SD Negeri 1 Tangkil -Ciambar - Mimit Sumitra; Siti Qomariyah (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This research aims to know the role of cooperation between the principal and teachers in improving teacher performance at SD Negeri 1 Tangkil. Effective collaboration is essential for creating a productive educational environment. The study employs a qualitative approach, utilizing interviews, observations, and document analysis for data collection. The findings reveal that open and collaborative communication significantly enhances teacher performance. The principal acts as a leader, providing direction, support, and motivation to teachers. Additionally, the principal serves as a mediator in resolving issues faced by teachers, fostering a harmonious work atmosphere. Furthermore, professional training and development programs initiated by the principal have proven to enhance teachers' competencies and confidence in their roles. However, challenges such as limited time for collaboration and differing visions between the principal and teachers remain obstacles to effective cooperation. In conclusion, strong collaboration between the principal and teachers not only improves individual teacher performance but also positively impacts the overall quality of education at SD Negeri 1 Tangkil.